(untitled) (PYC Nepal Journal of Management, 2024)
This study aims to explore the factors influencing the acceptance and intention to use (ITU) mobile banking (MB) among students at Tribhuvan University in Nepal, focusing on the roles of trust, security (SEC), social influence (SI), and service quality (SQ). The main analysis was performed on data from 460 respondents using structural equation modeling. The study utilized path analysis to examine the relationships between the variables, with attitude (ATT) toward use as a mediating factor. The results indicate that SQ significantly enhances students’ attitudes towards MB, which strongly influences their intention to use these services. Trust, SEC, and SI also positively impact the intention to use MB, although their effects are relatively modest. Interestingly, service quality does not directly affect ITU mobile banking, suggesting an indirect influence mediated by attitudes. The findings highlight the critical role of perceived service quality and positive attitudes in driving mobile banking adoption among university students. The study contributes to the theoretical understanding of MB adoption and offers practical insights for financial institutions to improve their services.